Determinants Of Interest In Young Muslim Investors Buying Retail Sukuk - Muhammad Ikhsan Harahap; Nurul Izzah; Rahmad Bahagia (Institut Agama Islam Negeri Padngsidimpuan, 2022)
Abstrak Perkembangan sukuk di Indonesia telah berkembang sangat pesat. Sukuk diharapkan menjadi alternatif pendanaan negara. Penelitian ini bertujuan untuk menganalisis determinan minat investor muda muslim dalam membeli sukuk ritel. Penelitian ini menggunakan data primer, sampel yang digunakan adalah 245 orang, dianalisis dengan Partial Least Squares (PLS). Hasil penelitian menunjukkan bahwa pengetahuan, return dan promosi berpengaruh minat investor muda muslim untuk membeli sukuk ritel. Untuk meningkatkan minat investor muda muslim untuk membeli sukuk ritel, otoritas sektor keuangan perlu memperkuat sistem keuangan dan pembangunan ekonomi di tanah air. Sementara itu, religiositas, harga, risiko investasi, atribut syariah, literasi keuangan, dan media sosial tidak mempengaruhi investor muda muslim dalam membeli sukuk ritel. Penelitian ini memberikan kontribusi terhadap keterbatasan pengetahuan mengenai determinan minat investor muda muslim dalam membeli sukuk ritel dengan menggali sembilan faktor yang meliputi faktor ekonomi dan non ekonomi. Abstract The development of sukuk in Indonesia has developed very rapidly. Sukuk are expected to be an alternative to state funding. This study aims to analyze the determinants of young Muslim investors' interest in buying retail sukuk.This study uses primary data, the sample used is 245 people, analyzed by Partial Least Squares (PLS).Research findings reveal that knowledge, returns and promotions influence the interest of young Muslim investors to buy retail sukuk.To increase the interest of young Muslim investors to buy retail sukuk, the financial sector authorities need to strengthen the financial system and economic development in the country. Meanwhile, religiosity, price, investment risk, Islamic attributes, financial literacy, and social media do not affect young Muslim investors in buying retail sukuk. This study contributes to the limited knowledge regarding the determinants of young Muslim investors' interest in buying retail sukuk by exploring nine factors including economic and non-economic factors.